PENGARUH KUALITAS PELAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN KONSUMEN PADA KEDAI LINTAS KOPI KOTA DEPOK JAWA BARAT - Syafiq Shiddiegy; Mada Faisal Akbar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine how much influence Service Quality and Store Atmosphere have on Consumer Satisfaction at Kedai Lintas Kopi, Depok City, West Java. The method used is a quantitative method with an associative approach. The population in this study were consumers at Kedai Lintas Kopi, Depok City, West Java. The sample collection technique used the Slovin formula which obtained a sample of 100 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that partially service quality has a significant effect on consumer satisfaction with the regression equation Y = 1,823 + 0,472 X1, the correlation coefficient value is 0.880 and the coefficient of determination value is 77.4% the remaining 22.6% is influenced by other factors. The hypothesis test obtained t count> t table or (18,336> 1.984). Thus Ho is rejected H1 is accepted. For store atmosphere, partial results show that store atmosphere has a significant effect on consumer satisfaction with regression Y = 6.111 + 0.826 X2, the correlation coefficient value is 0.880 and the determination coefficient value is 79,7%, the remaining 20,3% is influenced by other factors. Hypothesis testing obtained t count > t table or (19.587 > 1.984). The hypothesis test obtained t count > t table or (19,587 > 1,984). Thus, Ho is rejected and H2 is accepted. For the results of service quality and store atmosphere, they have a significant effect on consumer satisfaction with the regression equation Y = 2,247 + 0.359 X1 + 0.484 X2. The coefficient of determination is 83.6% while the remaining 16.4% is influenced by other factors. The hypothesis test F count value> F table or (247,615 > 3.09). Thus, Ho is rejected and H3 is accepte